A Rare Clinical Case Report of Hereditary Spherocytosis in a 17-Year-Old Female - Ganjala, Hemalatha; Padigala, Ramya Jyothi; Dimmiti, Jayasri; Gajula, Ram Nageswara Rao; Kollipara, Mohana (Indian Journal of Pharmacy Practice)
A congenital hemolytic condition called Hereditary Spherocytosis (HS) is caused by a lack of Red Blood Cells' (RBCs') plasma membrane protein. The hereditary condition is characterized by splenomegaly, jaundice, and anemia. We describe a case of a 17-year-old female patient who came to the surgical gastrointestinal department complaining of two days of abdominal pain. The patient also had a cold and cough for a few days, but these symptoms were unrelated to the main diagnosis. Laboratory investigations confirmed the diagnosis of hereditary spherocytosis. The patient underwent laparoscopic splenectomy and cholecystectomy as definitive management. Postoperatively, her symptoms resolved, and all the abnormal laboratory parameters normalized at the time of discharge. This case underscores the significance of early recognition and surgical management in enhancing outcomes for patients with hereditary spherocytosis.
Keywords: Hereditary spherocytosis; Jaundice; Plasma membrane protein; Congenital hemolytic; condition